Psychological risk indicators of disordered eating in athletes - Stoyel, H.; Shanmuganathan-Felton, V.; Meyer, C.; Serpell, L. (PLOS ONE, 2020)
Objectives: This project examined risk factors of disordered eating in athletes by adapting and applying a theoretical model. It tested a previously proposed theoretical model and explored the utility of a newly formed model within an athletic population across gender, age, and sport type to explain disordered eating. Design: The design was cross-sectional and the first phase in a series of longitudinal studies. Methods: 1,017 athletes completed online questionnaires related to social pressures, internalisation, body dissatisfaction, negative affect, restriction, and bulimia. Structural equation modelling was employed to analyse the fit of the measurement and structural models and to do invariance testing. Results: The original theoretical model failed to achieve acceptable goodness of fit (?2 [70, 1017] = 1043.07; p < .0001. CFI = .55; GFI = .88; NFI = .53; RMSEA = .12 [90% CI = .111-.123]). Removal of non-significant pathways and addition of social media resulted in the model achieving a parsimonious goodness of fit (?2 [19, 1017] = 77.58; p < .0001. CFI = .96; GFI = .98; NFI = .95; RMSEA = .055 [90% CI = .043-.068]). Invariance tests revealed that the newly revised model differed across gender, age, level, competition status, and length of sport participation. Conclusion: This study showed that the formation of disordered eating symptomology might not be associated with sport pressures experienced by athletes. It revealed that disordered eating development varies across gender, competition level, sport type, and age, which must be considered to prevent and treat disordered eating in athletes.